Evaluation of Acinetobacter baumannii antibiotic resistance from tertiary care hospital – Judging the silent storm (Panacea Journal of Medical Sciences, 2025)
Introduction: Over the closing decades, Acinetobacter baumannii has globally emerged as an enormously troublesome nosocomial pathogen. Its scientific importance has been in large part pushed through a fantastic cap potential to collect or upregulate numerous resistance determinants, making it one of the maximum a success multidrug-resistant (MDR) organisms threatening modern-day antibiotic therapy. On pinnacle of such captivating resistance acquisition, A. baumannii is endowed with more than one mechanisms of survival below a huge variety of environments, potentiating capability for health facility spread. The attributable mortalities in patients with A. baumannii healthcare-related infections, of which ventilator-related pneumonia and bloodstream infections are the maximum common, can variety from 5% in widespread health facility wards to 54% with inside the in depth care unit (ICU), with growing reviews of community-received A.baumanni infections. Mounting proof of extensively drug-resistant (XDR) and pandrug-resistant (PDR) isolates of A. baumannii is likewise gathering in different countries. The World Health Organization (WHO) has assigned A. baumannii as a vital precedence pathogen posing a wonderful risk to human health, and toward which new antibiotics are urgently needed.Aim & Objective: To evaluate various sample types from which Acinetobacter is isolated and evaluate antibiotic resistance pattern of Acinetobacter baumanii.Materials and Methods: This retrospective observational study has taken the data from January 2021 to June 2022. The data collection was done in the month of May 2023 followed by data analysis in June 2023 to July 2023. A total of 1058 Acinetobacter baumanii were isolated from January 2021 to June 2022 from various sample that come to microbiology department, which includes tissue, sputum, Blood, pus, swab, CSF, ET Tube, urine, drain, CVP/DLC tip and body fluids. The data was entered into Microsoft Excel (Windows 10), and analysis was performed using Microsoft Excel, including frequency distribution and percentage.Results: Out of 8226 (27.1%) positive culture 1058 ( 12.8%) were Acinetobacter baumannii isolates from various samples. highest resistance was seen with Ceftazidime (91.2%), followed by Piperacillin (88.5%), Ciprofloxacin (86.9%), Meropenem (82.6%), Imipenem (81.9%), Gentamicin (76.9%), Ampicillin-Sulbactam (68.6%), Amikacin (64.4%) and Tetracycline (57.5%). While Polymyxin B and Colistin was 100% sensitive.Conclusions: Guarded use of all antimicrobials needs to be done. As in our study also shows resistant to at least one antibiotic in three groups or more of the isolates.